2022
DOI: 10.1123/jtpe.2020-0294
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Physical Education in Early Years: Focusing on Teachers’ Practices

Abstract: Purpose: To examine early childhood teachers’ practices of teaching physical education. Method: Eleven early childhood educators participated in the study. Data were collected using two systematic observation instruments, a modified version of the Task Structure System and the Dynamic Model of Educational Effectiveness. Three 40-min lessons were observed for each teacher. The data were analyzed using descriptive statistics. Results: The findings showed that most childhood educators more often employed certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The results showed that students' physical education teaching under a single type of practice teaching mode was less effective, while the quality of physical education teaching combined with multiple teaching modes was better. Literature [12] analyzed the mode of physical education practice in early childhood education with 11 early childhood educators as an example, and early childhood physical education teachers used more narratives in the process of early childhood physical education teaching, while specific practices such as skill demonstrations were uncommon.…”
Section: Research Related To the Training Of Physical Education Major...mentioning
confidence: 99%
“…The results showed that students' physical education teaching under a single type of practice teaching mode was less effective, while the quality of physical education teaching combined with multiple teaching modes was better. Literature [12] analyzed the mode of physical education practice in early childhood education with 11 early childhood educators as an example, and early childhood physical education teachers used more narratives in the process of early childhood physical education teaching, while specific practices such as skill demonstrations were uncommon.…”
Section: Research Related To the Training Of Physical Education Major...mentioning
confidence: 99%
“…In order to deeply study and implement the spirit of the 19th CPC National Congress and further implement the requirements of the Opinions of the General Office of the State Council on Strengthening School Sports to Promote Students' Physical and Mental Health and Overall Development, comprehensively summarize, exchange and publicize the reform experiences, practices and achievements of the construction of school physical education teaching, training, competitions and conditions of the security system and other fields in recent years, and continuously accelerate the reform and development of school sports, the Ministry of Education The General Office of the Ministry of Education issued a notice on March 19, 2018 to collect reform results of the construction of school sports teaching, training, competition and condition guarantee system from all over the country. As of May 25, 441 achievements of various types were received from 29 provinces, autonomous regions, and municipalities directly under the central government [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, early childhood physical education has received more and more attention, and the construction of an effective and diversified physical education curriculum system is the key to improving the quality of early childhood physical education [1][2]. Kruskal algorithm, as a classical graph theoretic algorithm, is mainly used to solve the minimum spanning tree problem [3][4].…”
Section: Introductionmentioning
confidence: 99%